Strategic Foresight and Agility: Upholding Sustainable Competitiveness Among SMEs During COVID-19 Pandemic (International Journal of Economics and Management, 2022)
1. Arokodare, M. A. and Asikhia, O. U., 2020. Strategic Agility: Achieving Superior Organizational Performance through Strategic Foresight. Global Journal of Management and Business Research, 20(3), pp.7-16. https://doi.org/10.34257/gjmbravol20is3pg7 2. Auh, S. and Menguc, B., 2005. Balancing Exploration and Exploitation: The Moderating Role of Competitive Intensity. Journal of Business Research, 58(12), pp.1652-1661. https://doi.org/10.1016/j.jbusres.2004.11.007 3. Baskarada , S., Shrimpton, D., Ng, S., Cox, D. and Saritas, O., 2016. Learning through foresight. Foresight, 18(4), pp. 414–433. https://doi.org/10.1108/fs-09-2015-0045 4. Bereznoy, A., 2017. Corporate foresight in multinational business strategies. Foresight-Russia, 11(1), pp. 9–22.https://doi.org/10.17323/2500-2597.2017.1.9.22. 5. Brush, C. G., Greene, P. G. and Hart, M. M., 2001. From initial idea to unique advantage: The entrepreneurial challenge of constructing a resource base. Academy of Management Perspectives, 15(1), pp.64-78. https://doi.org/10.1109/emr.2002.1022409 6. Chen, W. H. and Chiang, A. H., 2011. Network agility as a trigger for enhancing firm performance: A case study of a high-tech firm implementing the mixed channel strategy. Industrial Marketing Management, 40(4), pp.643- 651. https://doi.org/10.1016/j.indmarman.2011.01.001 7. Chia, R., 2002. Essai: Time, duration and simultaneity: Rethinking process and change in organizational analysis. Organization Studies, 23(6), pp.863-868. 8. Economics and Development Resource Center (Asian Development Bank), Project Economic Evaluation Division Staff, 2003. Asian Development Outlook 2003. Oxford University Press, Incorporated. 9. Gerald, E., Obianuju, A. and Chukwunonso, N., 2020. Strategic agility and performance of small and medium enterprises in the phase of Covid-19 pandemic. International Journal of Financial, Accounting, and Management, 2(1), pp.41-50. https://doi.org/10.35912/ijfam.v2i1.163 10. Hashim, H. and Jumabhoy, A., 2017. Industry 4.0: SMEs are the vanguards in catalysing change. Insight, pp.33-34. 11. Kononiuk, A., 2017. Foresight in SME Companies. Journal of Machine Construction and Maintenance, 104, pp.109-115. 12. Kononiuk, Sacio-Szymanska and Gaspar, 2017. How do Companies Envisage the Future? Functional Foresight Approaches. Engineering Management in Production and Services, 9(4), pp.21-33. 13. Li, X., Chung, C., Goldsby, T. J. and Holsapple, C. W., 2008. A unified model of supply chain agility: The work‐ design perspective. The International Journal of Logistics Management, 19(3), pp. 408–435. https://doi.org/10.1108/09574090810919224 14. Lim, E. S. and Shyamala, N., 2007. Obstacles to innovation: evidence from Malaysian manufacturing firms. 15. Lin, J. (April 2020). Malaysia rolls out additional RM10 billion support for SMEs struggling due to Covid19 outbreak. Business Insiders. Retrieved 21 April 2020 from http://www.businessinsiders.my/malaysia 16. Mavengere, N. B. (2013). Information technology role in supply chain’s strategic agility. International Journal of Agile Systems and Management, 6(1), p. 7. https://doi.org/10.1504/ijasm.2013.052209 17. Mohtar, J. (April 2020). SMEs and Covid 19 – A ticking time bomb. The Malaysian Insight. Retrieved 20 April 2020 from https;//www.the malaysianinsight.com. 18. Muhyiddin, M. Y., 2020. Muhyiddin Mohd Yassin: Additional PRIHATIN SME Economic Stimulus Package (PRIHATIN SME+). [Online]. [Accessed 14 July 2021]. Available from: https://www.pmo.gov.my/wpcontent/uploads/2020/04/English-PM-Speech-PRIHATIN Plus-6-4-2020-905pm.pdf 19. Oyedijo, A., 2012. Strategic agility and competitive performance in the Nigerian telecommunication industry: An empirical investigation. American, International Journal of Contemporary Research, 2(3), pp.227-237. 20. Peter, M. K., and Jarratt, D. G., 2015. The practice of foresight in long-term planning. Technological Forecasting & Social Change, 101, pp.49-61. https://doi.org/10.1016/j.techfore.2013.12.004 21. Roberts, N. and Grover, V., 2012. Leveraging information technology infrastructure to facilitate a firm's customer agility and competitive activity: An empirical investigation. Journal of Management Information Systems, 28(4), pp.231-270. https://doi.org/10.2753/mis0742-1222280409 22. Rohrbeck, R., Battistella, C. and Huizingh, E., 2015. Corporate foresight: An emerging field with a rich tradition. Technological Forecasting and Social Change,101, pp.1-9. https://doi.org/10.1016/j.techfore.2015.11.002 23. Sardar, Z., 2010. Welcome to post-normal times. Futures, 42(5), pp.435-444. 24. Shin, H., Lee, J. N., Kim, D. and Rhim, H., 2015. Strategic agility of Korean small and medium enterprises and its influence on operational and firm performance. International Journal of Production Economics, 168, pp.181- 196. https://doi.org/10.1016/j.ijpe.2015.06.015 25. SME Annual Report (2018/19), Entreprenuership Driving SMEs, National Entrepenuer and SME Development Council (NESDC), Kuala Lumpur.